Correlation Analysis Between Vehicle Number and Meteorological Factors on Carbon Dioxide Concentration at Bojonegoro University - Purwaningrum, Solikhati Indah; Mulyanti, Heri; Amalia, Isna Nur; Anggraini, Sholikhah Risqi Dwi; Adriansyah, Endi (Universitas Hasanuddin, 2025)
The Bojonegoro University Campus area has a high level of vehicle traffic every hour, which makes it one of the locations where air pollution spreads. Bojonegoro University always has vehicle activities such as motorbikes and employee and student cars. This allows for increased exposure to CO2 ambient air pollutants around campus. The number of vehicles and meteorological conditions such as air humidity, temperature, and wind speed can influence air quality. The quality of the outside air is influenced by the large number of motorized vehicle activities and meteorology, which causes the spread of air pollution at Bojonegoro University. Air quality that exceeds quality standards impacts health, such as respiratory problems. The research method used is a quantitative descriptive approach. Based on the measurement results, the CO2 concentration is included in the polluted air category, namely in the range 403 - 514 ppm, while the quality standard set by WHO is 350-700 ppm. The influence between CO2 concentration and the number of motorized vehicles has a positive correlation value with a coefficient of 0.825. The impact of CO2 concentration on meteorological conditions includes temperature, air humidity, and wind speed. The correlation coefficient values for temperature, humidity, and wind speed are 0.825, -0.820, and -0.882. Therefore, the number of vehicles and meteorological conditions strongly correlate with CO2 concentrations in the ambient air.